Framing Theory on Cyber Politic Analysis: Candidate for Governor of North Sumatera on Instagram - Naila, Aisya Naifa; Gultom, Amanda Fransisca; Septiani, Arina Putri; Ulfa, Maryam; Avrillia, Wina; Putri, Dian Marisha (Universitas Pamulang, 2025)
This study explores the utilization of Instagram as a social media platform in political campaigns during the Medan Governor Election, applying the principles of framing theory. The primary aim is to investigate how gubernatorial candidates construct and disseminate their political messages through visual and textual content to shape voter perceptions. Anchored in Erving Goffman’s (1974) framing theory, the study examines how candidates selectively emphasize and organize information to influence audience interpretation. By employing Instagram features such as posts, stories, and interactive elements, candidates seek to craft their public image, underscore key issues, and engage voters effectively. The findings indicate that Instagram functions as a pivotal tool for shaping public opinion and increasing candidates' visibility in the context of digital media-driven political campaigns. This research underscores the importance of strategic social media use in modern political communication, highlighting its potential to redefine voter engagement and public discourse